2022
DOI: 10.1007/s44155-022-00028-8
|View full text |Cite
|
Sign up to set email alerts
|

Examining correlates of life satisfaction among Indian older adults using household fixed-effect approach

Abstract: Background Life satisfaction is one of the most important components of a person’s overall quality of life and a vital element of successful ageing. Few studies have previously attempted to investigate the level of life satisfaction among Indian older adults; however, the majority of them were at risk of omitted variable bias. This study, while controlling for household-level unobserved confounders, aims to investigate the correlates of life satisfaction among Indian older adults using househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Some demographic variables are important determinants of life satisfaction in old age. For example, according to a recent study, older age, higher education attainment, and higher self-rated health were associated with higher life satisfaction [ 27 ]. However, sex, marital status, and employment status did not predict life satisfaction in this study [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some demographic variables are important determinants of life satisfaction in old age. For example, according to a recent study, older age, higher education attainment, and higher self-rated health were associated with higher life satisfaction [ 27 ]. However, sex, marital status, and employment status did not predict life satisfaction in this study [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, according to a recent study, older age, higher education attainment, and higher self-rated health were associated with higher life satisfaction [ 27 ]. However, sex, marital status, and employment status did not predict life satisfaction in this study [ 27 ]. In addition, another study also demonstrated similar results, reporting that advancing age and higher economic conditions were associated with higher life satisfaction in old age [ 28 ].…”
Section: Introductionmentioning
confidence: 99%